Effectiveness of Shining Mind- A Smartphone App to Increase Mental Health Literacy Among College Students - Van, Vu Hong; Dao, Kieu Thi Anh; Minh, Dang Hoang (VNU Journal of Science: Education Research, 2020)
Background : Mental illness is a global public health challenge, particularly in low- and middle-income countries such as Vietnam. Improving mental health literacy was found to be associated with early detection and treatment of mental illness and increased help-seeking behaviors. With the development of information technology, IT applications such as websites and mobile applications have become essential tools for mental health literacy intervention. Though there has been a number of mobile apps delivering psychotherpies, little focus on mental health litracy intervention.   Aims: The study aims to a) evaluate the feasibility of a mobile-based mental health literacy intervention called Shining Mind and b) assess the effectiveness of the Shining Mind app in improving mental health literacy among college students. Methods : The study used randomized control trial design with two groups: experimental group (N=68) and control group (N=84). Results: The average number of times of accessing Shining Mind was 22.97 per student (SD=25.13) with one student (1.47%) never logging into the app. In terms of quality, the app was rated moderately good by participants (M=3.3, SD=0.6). Regarding mental health literacy, the results showed that there were group effects over time regarding depression and biopolar recognition, social anxiety labelling, stigma and parent help-seeking intention.